iReceipt : an intelligent expense tracker, based on receipt analysis and machine learning (B) - Tan, Chi Hui (Nanyang Technological University, 2020)
Expenditure tracking is a task which many people find tedious, but the main benefit is that it helps one achieves financial stability. Many people are unaware of the actual benefits of expenditure tracking and do not pick up the habit. The idea of encouraging more people to track their finances was the main objective of the project, and thus the development of iReceipt. This report entails the objectives, design and development of iReceipt, an intelligent expenditure tracking web application which aims to encourage users to track their finances by simplifying the tracking process. This is done by developing a web application which has Optical Character Recognition (OCR) functions to automate the process of tracking. By uploading the receipts, the application captures the details of the receipt and stores them into database. Users can view and search for their uploaded receipts as well as their expenditure for the month. They will also be able to set a monthly target expenditure to ensure that they spend within their budget.